Prognostic performance of neutrophil/lymphocyte ratio and platelet/lymphocyte ratio for mortality in patients with acute stroke - Cáceda-Samamé, R. F. (2024)
Objective: To evaluate the prognostic performance of the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) for mortality in patients with acute stroke treated at a Peruvian hospital. Design: Retrospective cohort study. Setting: Tertiary care hospital. Patients: Patients aged ≥18 years with a diagnosis of acute stroke and admitted to the hospital from May 2019 to June 2021. Interventions: None. Main variables of interests: Neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and mortality. Results: A total of 165 patients were included. The mean age was 66.1 ± 14.2 years, and 59.4% were male. Only NLR had a performance superior to 0.7 (AUC: 0.75; 95%CI: 0.65–0.85), and its elevated levels were associated with an increased risk of mortality (aRR: 3.66; 95%CI: 1.77–8.85) after adjusting for confounders. Conclusion: The neutrophil-to-lymphocyte ratio has an acceptable prognostic performance for mortality in patients with acute stroke. Its use may be considered to stratify patients’ risk and to consider timely alternative care and management.